Developing Inclusive Social Entrepreneurship Space: A Case Study of the CSR Program of PT. Pertamina EP Rantau Field Setara Sejalan - Putranto, Nurseno Dwi; Rahmadani, Rara Ayuni; Diltha, Khairunnisa; Isda, Dzakyansyah Naufal; Alfaruq, Fahmi Abdullah (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
Discussions about people with disabilities are often intertwined with stigma and negative societal paradigms. The government, as a policy maker, should ideally fulfill the rights of people with disabilities as citizens. However, it has not been effective in empowering this group, resulting in lower economic participation due to limited access to employment opportunities. This study aims to describe the efforts of PT Pertamina EP Rantau Field in creating an inclusive social entrepreneurship space for people with disabilities through the SETARA SEJALAN program. A descriptive qualitative method was employed, with data collection techniques including observation, interviews, and literature review. The findings indicate that PT Pertamina EP Rantau Field plays a crucial role in fostering inclusive social entrepreneurship as a means to fulfill the rights of individuals with disabilities. The company implements two main strategies: boosting self-confidence and developing businesses based on the concept of social entrepreneurship. The impact of the SETARA SEJALAN program extends beyond the disabled community, fostering a societal shift that transforms negative stigma into acceptance and collaboration with people with disabilities.